Examining the dynamics of ecological footprint in China with spectral Granger causality and quantile-on-quantile approaches - Alola, Andrew Adewale; Adebayo, Tomiwa Sunday; Onifade, Stephen Taiwo (Taylor & Francis, 2021)
With 2.5 global hectares (gha) per capita against 2.7 gha per capita, China’s ecological footprint is desirably below the world’s average ecological footprint per capita. Undesirably, the country’s per person ecological footprint outweighs the world’s average biocapacity per person of 1.7 gha, thus signifying an enormous pressure on the country’s ecological capacity. This reason accounts for the motivation to explore the dynamics of ecological footprint for China over the period 1971–2016 by employing a series of empirical techniques that include quantile-on-quantile regression (QQR), spectral Granger causality (SGC), and quantile regression. Indicatively, the empirical findings are in folds. First, from the QQR, economic growth exerts a positive effect on (i) ecological footprint especially in the middle quantile (0.4–0.7) and (ii) all quantiles (0.01–0.95) of economic growth. Second, both fossil fuel and primary energy utilization exert a positive impact on (i) all quantiles (0.01–0.95) of ecological footprint and (ii) all quantiles (0.01–0.95) of the two energy profiles. Third, it is surprising to see renewable energy utilization exerting a positive effect on ecological footprint at the lower tail (0.1–0.40) and on renewable energy use at the higher tail (0.70–0.95). Additionally, the SGC result revealed Granger causality from primary energy use and economic growth to the ecological footprint in the long-run without reverse. Additionally, without reverse, there is a Granger causality from renewable energy use to the ecological footprint in the short-, medium-, and long-term. Importantly, the overall policy implication suggests a more drastic decoupling of the country’s growth from the supply side (ecological pressure and environmental deprivation).
Keywords: Ecological deprivation; environmental sustainability; energy utilization; China; economic growth; fi=Taloustiede|en=Economics|